Pelatihan Desain Media Pembelajaran Berbasis Aplikasi Powerpoint Interaktif bagi Guru di SDN Inpres 3 Talise Kota Palu - Wahyuni H Mailili; Hajerina Hajerina (Jurnal Pengabdian UNDIKMA, 2022)
The purpose of this community service activity is to train on the develop teachers ability in creating  interactive powerpoint as learning medium for teachers at SDN  Inpres 3 Talise Palu City, Central  Sulawesi province. The methods used include lecturing, discussing and practicing. The steps of this community service program are 1) The stage of preparing and developing training materials; 2) Training and ; 3) Mentoring the practice . The results of the implementation of  the service  show that there is an in crease in the ability of  teachers at SDN Inpres 3 Talise  in developing knowledge, comprehension, professionalism and creativity in designing interactive powerpoint as a medium for learning mathematics in elementary schools.